2018
DOI: 10.11648/j.ajbes.20180402.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Advanced Bread Wheat Lines for Field and Seedling Resistance to Stem Rust (<i>Puccinia graminis</i> f. sp. <i>tritici</i>)

Abstract: Field-based adult plant resistance assessment at multi-location rust hot spot sites is a crucial job for those plant pathologists screening several wheat lines at a time against the rusts. Rust resistant bread wheat genotypes that have been extracted from previous studies have sustained wheat production in Ethiopia. The objective of this study was to evaluate advanced bread wheat lines extracted from wheat breeding trials against stem rust at adult plat stage under stem rust hot spot sites and at seedling stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…On the other hand, the susceptible check Morocco and four ETBW-8802,ETBW 8668, ETBW-8595 and ETBW-9557, and two ETBW-8668 and ETBW-9557 tested genotypes displayed ACI above 41 Table 2 Information's of this study disclosed that 22 wheat genotypes namely showed acceptable level of stem rust slow rusting in both diseases assessment parameters, terminal rust severity and average coefficient of infections during 2018 growing season at both locations compared with Morocco (universal susceptible check).These wheat lines were found to be resistant to stem rust disease and can be used in breeding programs to release commercial cultivars as safely production under Ethiopian conditions. The result of this study is in agreement with Bekele Hundie et al (2018), who reported advanced bread wheat lines extracted from wheat breeding trials against stem rust at adult plat stage under stem rust hot spot sites and at seedling stages in the greenhouse. In addition, the result of this study is in lined with the works of Nzuve F. (2012) who reported as evaluating wheat genotypes for both field and seedling resistance to stem rust and genotypes showed diverse seedling and adult plant resistance responses.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, the susceptible check Morocco and four ETBW-8802,ETBW 8668, ETBW-8595 and ETBW-9557, and two ETBW-8668 and ETBW-9557 tested genotypes displayed ACI above 41 Table 2 Information's of this study disclosed that 22 wheat genotypes namely showed acceptable level of stem rust slow rusting in both diseases assessment parameters, terminal rust severity and average coefficient of infections during 2018 growing season at both locations compared with Morocco (universal susceptible check).These wheat lines were found to be resistant to stem rust disease and can be used in breeding programs to release commercial cultivars as safely production under Ethiopian conditions. The result of this study is in agreement with Bekele Hundie et al (2018), who reported advanced bread wheat lines extracted from wheat breeding trials against stem rust at adult plat stage under stem rust hot spot sites and at seedling stages in the greenhouse. In addition, the result of this study is in lined with the works of Nzuve F. (2012) who reported as evaluating wheat genotypes for both field and seedling resistance to stem rust and genotypes showed diverse seedling and adult plant resistance responses.…”
Section: Resultssupporting
confidence: 92%
“…The genotypes were evaluated in alpha lattice design with three replications at four environments (Kulumsa, Asasa, Dhere and Melkasa Research sites) for two consecutive main cropping seasons (2017/18-2018/19). In both years each genotype was sown with six rows of 2.5m length with 0.2m space between the rows, being plot size of 3m 2 . Six rows were harvested and the net harvested plot was 3m 2 (2.5m x 1.2m).…”
Section: Experimental Plot Design For Yield Assessmentmentioning
confidence: 99%
“…In both years each genotype was sown with six rows of 2.5m length with 0.2m space between the rows, being plot size of 3m 2 . Six rows were harvested and the net harvested plot was 3m 2 (2.5m x 1.2m). Field management and agronomic practices were carried out as recommended for each location.…”
Section: Experimental Plot Design For Yield Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many new variants of Pgt were first identified in this country and spread to different parts of the world. Rust of wheat, races TTKSK, TKTTF, TRTTF, JRCQC, and TTTTF are the stem rust of wheat races that are threatening wheat production currently in Ethiopia [16]. In 2013/2014, severe stem rust epidemics were caused by Pgt race TKTTF (not a member of Ug99 lineage) resulting in nearly total yield loss on widely grown wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%